Два разных воплощения нечистой силы в повестях Н. В. Гоголя «Вий» и «Портрет» - Czumft, Réka (Vilnius University Open Series, 2024)
In the article, the forms of the personification of impure forces are analyzed based on the materials of two N. V. Gogol’s short stories named Viy and The Portrait. The image of the devil in Gogol’s works is diverse, so we are making an attempt to identify the specifics of his image in these stories. The article examines in detail the spatial structure of the two plots, their dynamics, changes in values and the embodiment of evil spirits at the lexical level. A comparison of the two works in these aspects will help to better understand the evolution of the depiction of evil spirits in Gogol’s work.
Keywords: Гоголь; черт; нечистая сила; оппозиции; взгляд